Quality characteristics and sensory profile of stirred yogurt enriched with papaya peel powder - Manzoor, Sama; Yusof, Yus Aniza; Chin, Nyuk Ling; Mohamed Amin Tawakkal, Intan Syafinaz; Ahmed, Mohamed Fikry Mohamed; Chang, Lee Sin (Universiti Putra Malaysia Press, 2019)
Dietary fibre enriched food is gaining more popularity due to their numerous health benefits. In this study, papaya peel powder was prepared as a source of dietary fibre to be fortified in yogurt at different concentrations (1.5 and 3.0 % w/w). Papaya peel was dried at three different temperatures (45, 55 and 65°C) and the results showed that drying at temperature of 55 and 65°C was able to retain higher total dietary fibre content of 40.21 and 48.00 g/100 g, respectively, and was used for enrichment in yogurt. The quality characteristics in terms of viscosity, pH and colour (L*, a*, b*, chroma, hue angle and total colour difference) of stirred yogurt added with papaya peel powder stored at 4°C was investigated weekly up to 21 days. Sensory evaluation (9-point hedonic scale) was also conducted for the yogurt samples prepared. Results showed the viscosity of yogurt was higher when the amount of papaya peel powder added was increased. It also showed an increasing trend during 21 days of storage. The pH values of the samples prepared had no significant difference (P > 0.05) as the concentration of powder was raised. However, a notable reduction in pH was observed after storage. Colour parameters were also significantly affected (P < 0.05) by the addition of powder, with fortified samples exhibiting darker (lower L* value) and more yellowish (higher b* value) colour than the control sample. Nonetheless, the parameters remained unchanged during storage of 21 days. Sensory results revealed that the stirred yogurt with 1.5% concentration of papaya peel powder dried at 55°C received the highest sensory scores among other samples.